UJI VIABILITAS DAN PERKEMBANGAN SERBUK SARI BUAH NAGA PUTIH (HYLOCEREUS UNDATUS (HAW.) BRITTON & ROSE), MERAH (HYLOCEREUS POLYRHIZUS (WEB.) BRITTON & ROSE) DAN SUPER MERAH (HYLOCEREUS COSTARICENSIS (WEB.) BRITTON & ROSE) SETELAH PENYIMPANAN - SARI, NI KADEK YUNITA; KRISWIYANTI, ENIEK; ASTARINI, IDA AYU (Jurnal Biologi Udayana; Vol 14 No 2 (2010): Jurnal Biologi, 2010)
The aim of the research was to determine pollen viability, pollen tube length and pollen development of white, red and super red dragon fruit after storage at different temperatures and times. The method used to test pollen viability was hanging drop technique and to observe the development of pollen used acetolysis techniques. The results showed viability and pollen tube length of white, red and super red dragon fruit after storage at temperature of 10° C and -20° C for 1, 2 and 3 weeks decreased (66% and 25%), tended to increase (2% ) after 4 weeks. Viability and pollen tube length decreased (100%) after storage at 30° C for 4 weeks. Pollen development of white, red and super red dragon fruit after storage at 30°C, 10°C and -20°C for 1 to 4 weeks showed the majority of pollen consists of uninucleat and binucleat.
Keywords: viability, pollen, hanging drop, development, storage